Pioneer Teachers’ Professional Identity Construction: Self-Efficacy and The Praxis Shock of Teachers’ Experiences - Siti Nur'Aini; Listyaning Sumardiyani; Panithi Amatayakul; Laily Nur Affini; Nuning Zaidah (FKIP Universitas Lampung, 2026)
This study examines the formation of professional identity among teachers who participated in the Pioneer Teacher Program (PT Program) through the lens of self-efficacy and their responses to changes in their environment and mindset. This research used a mixed-methods approach, combining quantitative and qualitative data to provide a comprehensive understanding of their experiences. A total of 89 participants from various regencies were involved, representing a diverse range of backgrounds and teaching contexts. Quantitative data were analyzed using ANOVA to measure the self-efficacy of teachers across the group of pioneer teachers, candidates of pioneer teachers, and instructors of pioneer teachers. The qualitative and other supporting data from interviews, open-ended responses, and the researchers’ notes were analyzed thematically using MAXQDA to gain deeper insights into the teachers’ construction of professional identity. The ANOVA analysis indicates no statistically significant differences across the measured competencies among the groups. The results were informed by evidence that all participants have equally strong backgrounds prior to joining the training program. While pioneer teachers demonstrate moderate to high levels of self-efficacy and digital skills, the formation of their professional identity is shaped more profoundly by mentorship experiences and community engagement. The way teachers changed their mindset in the classroom practice after joining the program, and they started to decompartmentalize their teaching. They transitioned from traditional, content-focused teaching to lead a more student-centered classroom and to adopt approaches that strengthen students’ character. Despite differences in regional contexts, a common theme emerged: participants began to see themselves not just as educators, but as change agents and instructional leaders. The study highlights the importance of systemic support and ongoing professional development in fostering sustainable identity transformation among teacher leaders. Keywords: pioneer teachers, pioneer teachers’ program, professional identity, self-efficacy.